Carbon-based Materials for Sustainable Energy Innovations: Recent Advances and Future Challenges - Sari Yusuf, Andi Asdiana Irma; Taspika, Melda (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2021)
Sustainable energy is essential to reduce fossil fuel consumption. However, sustainable energy development still faces many problems that make its progress insignificant in the last decades. Alternative energy sources are needed to minimize fossil fuels (coal, natural gas, and petroleum). Biomass and carbon fullerenes are a choice, but their innovation technologies are still restricted to pilot-scale production in the laboratory. Biomass is a climate-neutral energy source, but the CO2 emission of biomass combustion is inevitable, indicating the importance of innovative methods in processing biomass to energy. Different methods (thermochemical or biochemical) will produce different carbon footprints. Besides, biomass development also requires innovative small-scale technology to generate affordable energy for citizens and communities. Carbon fullerenes have been applied for energy applications, especially capacitor and lithium-ion (Li-ion) batteries. Up today, progress in Li-ion battery manufacturing moves at a slower pace and not much progress. The significant problems of Li-ion batteries are volume expansion, low electric conductivity, and inappropriate coulombic efficiency. Carbon-based fibers such as carbon nanofibers, CNT-based fibers, and graphene-based fibers have been used for capacitors, but there are still many obstacles, such as a lack of knowledge to solve capacitor self-discharging. Therefore, research and development of carbon-based materials are urgent energy innovation developments.